ChemInform Abstract: Palladium‐Catalyzed Enantioselective Decarboxylative Cycloaddition of Vinylethylene Carbonates with Isocyanates. Issue 22 (15th May 2015) - Khan, Ajmal; Xing, Juxiang; Zhao, Jingming; Kan, Yuhe; Zhang, Wanbin; Zhang, Yong Jian
Abstract: The prepared cyclic carbamates can be converted to β‐vinylglycinols in two steps.